Ames Assay Transferred from the Microtiter Plate to the Planar Assay Format - Katharina Schmidtmann; Johanna Lemme; Gertrud E. Morlock (Journal of Xenobiotics)
The International Agency for Research on Cancer has studied and classified 1045 potential substances. It is therefore important to develop rapid screening methods to identify the mutagenicity of compounds and, further on, the intensity and number of individual mutagenic substances in complex sample mixtures. The current in vitro Ames assay in the microtiter plate format (MPF) uses a pH-sensitive detection as endpoint, however, acidic substances in complex mixtures may interfere the mutagenicity result. Hence, it was transferred to the planar assay format to be more selective for complex mixture testing. The co-culture of Salmonella Typhimurium strains TA98 and TA100 with an optical density of 0.4 at 600 nm was applied on a high-performance thin-layer chromatography silica gel 60 chromatogram and on-surface incubated for 5 h, which period was limited due to zone diffusion. Various positive controls were tested, and 4-nitrochinolin-N-oxide with a limit of detection of 100 ng was established as a positive control. However, due to the shorter incubation time, no mutagenic compounds were detectable or differentiable in the tested perfumes, herbal teas, margarines, and hand creams. This does not mean that the samples are mutagen-free, but it suggests that further improvements to the bioassay are urgently needed to increase the sensitivity and selectivity of the response. Compared to conventional sum value assays, a planar Ames assay performed on the separated and adsorbed sample components advances toxicology research because mutagenic compounds are separated from interfering molecules due to the integrated separation. It thus would provide a more selective detection of mutagens in complex mixtures and allow testing of large sample volumes or concentrated samples without matrix interference.